Uma análise sobre os direitos humanos nas práticas curriculares da formação de psicólogos (as) da UFPA (2011-2015) - FRANCO, Ana Carolina Farias (Universidade Federal do Pará, 2017)
This thesis had as objective to problematize the curricular practices of the training in Psychology of the Federal University of Pará (UFPA), in order to investigate how it is the produced in this curriculum the object human rights between the years 2011 and 2015. Specifically aimed at problematizing the object human rights and its relation to field of education, examining the rationalities about human rights education today; to question the ways in which the human rights object has materialized in the practices of Brazilian psychology; to analize the way in which human rights objects is present in the curriculum devices: National Curricular Guidelines for the Psychology Courses and Political Pedagogical Project of the UFPA Psychology Course; to analize the rationalities about human rights present in the academic production of the Faculty of Psychology at UFPA and the relationship with the discourse societies to which they belong. From the Post-Critical Studies of the curriculum, we consider that the curriculum should not be thought of as merely a technical instrument that educational institutions produce to organize the disciplinary contents, but as a political device that produces effects of truth and power. Thus, in our analysis, we assume that the human rights object in the formation of psychologists is produced in a political framework in the construction of the curriculum, in which the struggle for the definition of this object is linked to different fields of knowledge and practices of subjectivation. What political rationales about human rights education are in dispute today? How have the practices of Brazilian psychology approached the field of human rights? How are human rights addressed by the National Curriculum Guidelines for Psychology Courses and by the Political Pedagogical Project of the UFPA Psychology Course? How are the rights addressed in the teaching production of the Faculty of Psychology of the mentioned university and to what rationalities appear related? As an initial hypothesis, it was argued that the curricular practices of the Psychology Training, offered by the Federal University of Pará, in the period of 2011-2015, are disconnected from the national propositions for Human Rights Education in Higher Education, although a set of existing Government Resolutions and Plans and the incentive to include human rights in Psychologist Training promoted by Psychology Entities, such as the Brazilian Association of Teaching Psychology and Federal Counsel of Psychology. And yet, although it is not a transversal axis of this formation, Human Rights are an object present in the curriculum, whose emergence occurs amidst a dispute for the definition and validation of this object between the different epistemological perspectives that sustain this curriculum. As far as the methodological aspects are concerned, a bibliographical and documentary research was carried out, starting from a historical perspective, prioritizing the intersection between the tracks of the archaeogenealogical history proposed by Michel Foucault and the historical ruptures engendered by the Annales (French school of historiography). As primary sources, in addition to the literature on training in Psychology and national and international documents on Human Rights Education, we favor CNE / CES Resolution nº 08/2004, which establishes the National Curricular Guidelines for Psychology Courses; the Resolution of the CONSEPE / UFPA n ° 4.216 / 2011 that regulates the political project pedagogical of the Course of Psychology; Course Plan of the Discipline Psychology, Justice and Human Rights; the curriculum lattes of 32 teachers linked to the Faculty of Psychology and; articles published in periodicals and chapters of books produced by these teachers between the years of 2011 to 2015. In the comparison between documentary sources, it was concluded that although the Political Pedagogical Project of the Psychology Course does not present human rights education with a transverse axis of formation, this object emerges strongly in a moving curriculum. This assertion was constructed from the analysis of the expressive teaching production, we analyse that the fabrication is in the dispute for distinct political rationalities, whose effects of power-knowledge-subjectivation can both affirm the rights as processes of singularization, as well as to support the judicialization and medicalization of life through of the curricular policy put into circulation in the Course of Psychology of the Faculty of Psychology of the Institute of Philosophy and Human Sciences of the Federal University of Pará.